Economic relations EU-China - the mechanism that the European Union outlines the position of the economic actor - Loredana Jitaru; Lorena Florentina Popescul (CES Working Papers, 2017)
Both the EU and China face a number of challenges. The EU has reached the pinnacle of international identity and is going through a rather difficult process of rethinking it. Regarding China, this actor goes through a phase of rethinking its economic growth model, namely the transition from an economy based, in greater extent on exports and investment to an economic growth based on stimulating domestic consumption. In this context, in order to meet the challenges of the third millennium and beyond, the two actors need to strengthen their cooperative relations as they are vital in solving the challenges of this millennium. This paper aims to provide an overview of EU-China economic relations and to analyse the impact of these relations on the EU economy.
Keywords: 330; foreign direct investment; economic actor; EU-China cooperation relations